MMP-1 activation contributes to airway smooth muscle growth and asthma severity - Naveed, Shams-un-nisa; Clements, Debbie; Jackson, David J.; Philp, Christopher; Billington, Charlotte K.; Soomro, Irshad N.; Reynolds, Catherine; Harrison, Timothy W.; Johnston, Sebastian L.; Shaw, Dominick E.; Johnson, Simon R. (American Thoracic Society, 2017)
Introduction: Matrix metalloproteinase-1 and mast cells are present in the airways of people with asthma. We hypothesised that matrix metalloproteinase-1 could be activated by mast cells and increase asthma severity. Methods: Patients with stable asthma and healthy controls underwent spirometry, methacholine challenge, bronchoscopy and their airway smooth muscle cells were grown in culture. A second asthma group and controls had symptom scores, spirometry and bronchoalveolar lavage before and after rhinovirus-induced asthma exacerbations. Extra-cellular matrix was prepared from decellularised airway smooth muscle cultures. Matrix metalloproteinase-1 protein and activity were assessed. Results: Airway smooth muscle cells generated pro-matrix metalloproteinase-1 which was proteolytically activated by mast cell tryptase. Airway smooth muscle treated with activated mast cell supernatants produced extra-cellular matrix which enhanced subsequent airway smooth muscle growth by 1.5 fold (p<0.05) which was dependent on matrix metalloproteinase-1 activation. In asthma, airway pro-matrix metalloproteinase-1 was 5.4 fold higher than control subjects (p=0.002). Mast cell numbers were associated with airway smooth muscle proliferation and matrix metalloproteinase-1 protein associated with bronchial hyper-responsiveness. During exacerbations, matrix metalloproteinase-1 activity increased and was associated with fall in FEV1 and worsening asthma symptoms. Conclusions: Matrix metalloproteinase-1 is activated by mast cell tryptase resulting in a pro-proliferative extra-cellular matrix. In asthma, mast cells are associated with airway smooth muscle growth, matrix metalloproteinase-1 levels are associated with bronchial hyper-responsiveness and matrix metalloproteinase-1 activation with exacerbation severity. Our findings suggest that airway smooth muscle/mast cell interactions contribute to asthma severity by transiently increasing matrix metalloproteinase activation, airway smooth muscle growth and airway responsiveness.